Kepemimpinan Transformasional dalam Membangun Kinerja Guru di Sekolah Dasar - Darul Amin; Nasir Usman; Ismail; Rahmat Saleh (LPPM Undiksha, 2025)
This research is motivated by low levels of learning innovation, lack of work motivation, and the suboptimal implementation of teachers' professional duties. These conditions are thought to be related to the suboptimal implementation of transformational leadership by principals. This study aims to analyze the transformational leadership of principals in efforts to improve teacher performance in elementary schools. The study used a qualitative descriptive approach with a case study design involving principals and teachers. The subjects of this study were principals and elementary school teachers. Data collection techniques were carried out through interviews, observation, and documentation. Then, data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Validation was carried out through triangulation of sources and methods. The results showed that principals implemented three dimensions of transformational leadership: idealized influence, inspirational motivation, and intellectual stimulation, which were reflected in role models, providing motivation, and encouraging innovation and individual attention. The implementation of this leadership had a positive impact on teacher discipline, creativity in the learning process, and work enthusiasm. Therefore, it was concluded that transformational leadership has an important role in improving teacher performance and the quality of education in elementary schools. The implication is that this research can be a reference for educational policy makers in developing leadership development and training programs in elementary schools.